Pengaruh Fungisida terhadap Pertumbuhan Jamur Colletotrichum gloeosporioides Secara in vitro - I Wayan Diksa Gargita (Fakultas Pertanian, Universitas Udayana, 2024)
Anthracnose is an important disease of garlic (Allium ascalonicum) caused by the fungus Colletotrichum gloeosporioides. This study aims to test the inhibition of fungicides made from mancozeb, carbendazim, and tebuconazole. This test used 70% mancozeb, 10% carbendazim, and 50% tebuconazole which was conducted using the Poisoned Food Technique method. Testing the inhibition of each fungicide against the growth of the fungus C. gloeosporioides was carried out in a completely randomized design (CRD) with concentrations, namely: 0.000 ml/l (F0), 0.094 ml/l (F1), 0.188 ml/l (F2), 0.375 ml/l (F3), 0.75 ml/l (F4), and 1.5 ml/l (F5). The data obtained were analyzed using SPSS software version 28.0 with the ANOVA (Analysis of Variance) method. Followed by Duncan Multiple Range Test (DMRT) test at 5% level if there is a significant difference. The results showed that all active ingredients of fungicides were able to suppress fungal growth seen from the colony area and growth rate of fungal colonies. Fungicides made from mancozeb 70% can inhibit the growth of C. gloeosporioides fungi in vitro at concentration levels of 0.094 ml/l to 1.5 ml/l, made from carbendazim 10% can inhibit the growth of C. gloeosporioides fungi in vitro at concentration levels of 0.094 ml/l to 1.5 ml/l, and made from tebuconazole 50% can inhibit the growth of C. gloeosporioides fungi in vitro at concentration levels of 0.094 ml/l to 1.5 ml/l.